Stapedoplasty – surgical treatment of hearing loss caused by otosclerosis - Šaboviča, Jeļena; Klagiša, Renāta (Social Welfare: Interdisciplinary Approach, 2016)
Otosclerosis is a condition of abnormal bone growth around the stapes bone, one of the tiny bones of the middle ear. This leads to a fixation of the stapes. The stapes bone must move freely for the ear to work properly and hear well. Hearing loss is the most functional deficit caused by otosclerosis. However, tinnitus (noise or ringing in the ears) is frequently reported by otosclerotic patients, especially in those patients with inner ear involvement. The best therapy in achieving a significant improvement is surgical repair of the stapes – stapedoplasty. Analysis of early hearing results (1 month after surgery) shows efficiency of surgical treatment and improvement in hearing.
Keywords: audiogram; hearing loss; otosclerosis surgery; stapes akylosis; stapedoplasty